PELAKSANAAN KOORDINASI DALAM REVITALISASI JALUR LAMBAT PASAR PAGI ARENGKA - Eva Nurlina; Evi Zubaidah (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
This study aims to determine the level Implementation Coordination destination Slow Path In Morning Market Revitalization Arengka. Coordination of assessment indicators used include Settings, Synchronization (unify), Shared Interests and Objectives Together. The location was used in this study is the Department of Transportation and Communications and Information Technology Department of the General Workers Pekanbaru. This type of research is Diskriptif Survey, which prioritizes data collection questionnaire tool list and a list of guidelines for the interview as a basic tool to explain the variable and its influence starting from the use of such data. There are two groups of the population and sample in this research is the field of Highways and the Supervision and Control of Traffic totaled 13 people and employees of the Supervision and Control of Traffic Pekanbaru total of 11 people. Three sampling technique used in determining individual sample was purposive sampling technique for population Head of Public Workers, Head of Communications and Informatics, Head of Highways and Head of Supervision and Control of Traffic. Saturated Sampling Technique / Census for population groups of employees field of Highways and Employee Monitoring and Controlling Pekanbaru. Types and data collection techniques consist of primary data and secondary data. Data analysis technique used is by using descriptive method which is a way to analyze the available data on the object of research and comparing with the theory-related problems. Furthermore, both quantitatively analyzed further to compare the reality with existing references in the analysis associated with this study in the form of a brief and clear description. Based on analysis techniques researchers assess and conclude that the Implementation Coordination In Slow Path Morning Market Revitalization Arengka quite accomplished.